Crop water status estimated by remote sensing information - Palumbo A.D.; Campi P.; Modugno F.; Mastrorilli M. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Techniques to more accurately quantify crop water status are needed for determining crop water requirements and appropriate irrigation scheduling. Remote sensing techniques are a possible tool for estimating the crop water status. To verify this hypothesis, in 2007 a measurement campaign was carried out in Rutigliano (lat. 41°01' N, long. 17°01 E, alt. 147m a.s.l.), with the tomato as the test crop. This crop was subjected to three irrigation treatments. To monitor the water status, both remote sensing (NDVI and radiative surface temperature) and manual measurements (stomatal conductance and pre-dawn leaf water potential (PLWP)) were used. The NDVI index is a function of both crop growth (LAI and biomass) and the crop water status. The experimental data showed a linear relationship between PLWP and NDVI. From this relationship it seems possible to predict the crop water status starting from completely automatic measurements. Although additional research is needed, the remote sensing technique potentially offers an improvement of the irrigation scheduling.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)